Manajemen Nyeri Pasca Operasi Orif Femur dengan Epidural Anestesi - Dewa Gede Aginta Putra Adiatmika; Halima Aulia Ita Maghfiroh (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Background: Post operative pain is a common clinical effect found in patients undergoing surgical procedures that are usually seen in the first 24-48 hours after surgery so that it is included in acute pain. Methods: This study is a descriptive observational study of five patients with ORIF femur surgery who underwent surgery at Pandan Arang Boyolali Hospital using epidural anesthesia. Results: five patients successfully underwent epidural anesthesia as one of the anesthesia used with major surgery and as an option for continuous anesthetic drug administration and used as post-surgical pain management. Conclusion: Epidural analgesic administration can also be done using a syringe injector attached to the patient as one of the post-surgical pain management in patients.